Chemical elicitation as an avenue for discovery of bioactive compounds from fungal endophytes - Munusamy, Madhaiyan; Ching, Kuan Chieh; Yang, Lay Kien; Crasta, Sharon; Gakuubi, Martin Muthee; Chee, Zhao Yan; Wibowo, Mario; Leong, Chung Yan; Kanagasundaram, Yoganathan; Ng, Siew Bee (Frontiers in Chemistry, 2022)
The present study investigated the molecular phylogeny, antimicrobial and cytotoxic activities of fungal endophytes obtained from the A*STAR Natural Organism Library (NOL) and previously isolated from Sungei Buloh Wetland Reserve, Singapore. Phylogenetic analysis based on ITS2 gene suggests that these isolates belong to 46 morphotypes and are affiliated to 23 different taxa in 17 genera of the Ascomycota phylum. Colletotrichum was the most dominant fungal genus accounting for 37% of all the isolates, followed by Diaporthe (13%), Phyllosticta (10.9%) and Diplodia (8.7%). Chemical elicitation using 5-azacytidine, a DNA methyltransferase inhibitor and suberoylanilide hydroxamic acid, a histone deacetylase inhibitor resulted in an increase in the number of active strains. Bioassay-guided isolation and structural elucidation yielded pestahivin and two new analogues from Bartalinia sp. F9447. Pestahivin and its related analogues did not exhibit antibacterial activity against Staphylococcus aureus but displayed strong antifungal activities against Candida albicans and Aspergillus brasiliensis, with IC50 values ranging from 0.46 ± 0.06 to 144 ± 18 µM. Pestahivin and its two analogues furthermore exhibited cytotoxic activity against A549 and MIA PACA-2 cancer cell lines with IC50 values in the range of 0.65 ± 0.12 to 42 ± 5.2 µM. The finding from this study reinforces that chemical epigenetic induction is a promising approach for the discovery of bioactive fungal secondary metabolites encoded by cryptic gene clusters.